THE BISOPROLOL — A HIGH SELECTIVE BETA-BLOCKER ACCORDING TO EVIDENCE BASED MEDICINE - Yu. V. Lukina; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
Data of the evidence based medicine about bisoprolol treatment of patients with cardiovascular diseases (arterial hypertension, ischemic heart disease, chronic heart failure, rhythm disorders) are presented. Implementation of bisoprolol generics as well as bisoprolol usage in smoking cardiovascular patients is also discussed.